2017
DOI: 10.1093/jac/dkx326
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of minor groove binders (MGBs) as novel anti-mycobacterial agents and the effect of using non-ionic surfactant vesicles as a delivery system to improve their efficacy

Abstract: MGB anti-mycobacterial activities together with non-toxic properties indicate that MGB compounds constitute an important new class of drug/chemical entity, which holds promise in future anti-TB therapy. Furthermore, the ability of NIVs to better deliver entrapped MGB compounds to an intracellular Mtb infection suggests further preclinical evaluation is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 41 publications
1
19
0
Order By: Relevance
“…11 Importantly, our S-MGBs do not possess any alkylating moieties and we hypothesise that their mechanism of action against cancer cells is similar to that observed in our ongoing studies of anti-bacterial and anti-parasitic S-MGBs which suggest non-covalent interruption of DNA functions. [19][20][21] Moreover, we have previously demonstrated that S-MGBs 4, 74 and 317 do bind to DNA giving ΔTms of 7, 4 and 7 o C, respectively. 9 However, it was important to establish whether these lead anti-cancer S-MGBs induce significant DNA damage or not and thus whether these might suffer from similar toxicity issues as alkylating anti-cancer MGBs.…”
Section: Assessment Of Dna Damagementioning
confidence: 99%
“…11 Importantly, our S-MGBs do not possess any alkylating moieties and we hypothesise that their mechanism of action against cancer cells is similar to that observed in our ongoing studies of anti-bacterial and anti-parasitic S-MGBs which suggest non-covalent interruption of DNA functions. [19][20][21] Moreover, we have previously demonstrated that S-MGBs 4, 74 and 317 do bind to DNA giving ΔTms of 7, 4 and 7 o C, respectively. 9 However, it was important to establish whether these lead anti-cancer S-MGBs induce significant DNA damage or not and thus whether these might suffer from similar toxicity issues as alkylating anti-cancer MGBs.…”
Section: Assessment Of Dna Damagementioning
confidence: 99%
“…3.1.Summary of a study of MGBs as drugs in the fight against the Mycobacterium tuberculosis (Mtb) disease [51]: Mycobacterium tuberculosis (Mtb), is a crucial subject as it is among the top infectious illnesses around the world. The world health organisation in 2016 [39] reported that TB killed around 1.8 million people in 2015, that is an increase from 1.5 million deaths in 2014 [40] .…”
Section: Resultsmentioning
confidence: 99%
“…There are several reports showing NIVs to be a promising inhalable drug delivery system for the treatment of pulmonary aspergillosis with aerosolized amphotericin. Amphotericin B/NIV administration lowered fungal lung infection when it was compared with amphotericin B solution alone [48][49][50][51][52].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These structural variants retained DNAbinding and anti-Gram-positive activity but lacked human toxicity [6]. One of these, MGB-BP-3 ( Figure 1a found to be active against a wide variety of pathogens and some cancer cell lines [7][8][9][10][11]. Antibacterial activity of MGB-BP-3 is confined to Gram-positive bacteria and dose response curves show a steep decrease in viability over a narrow concentration range, suggesting a catastrophic failure in the bacterium rather than an interaction with a single receptor typified by a sigmoidal dose-response curve.…”
Section: Introductionmentioning
confidence: 99%